Human Recombinant Fab Fragment Neutralizes Shiga Toxin Type 2 Cytotoxic Effects in vitro and in vivo - Luz, Daniela (Toxins (Basel), 2018)
Shiga toxin (Stx) producing Escherichia coli (STEC) is responsible for causing hemolytic uremic syndrome (HUS), a life-threatening thrombotic microangiopathy characterized by thrombocytopenia, hemolytic anemia, and acute renal failure after bacterially induced hemorrhagic diarrhea. Until now, there has been neither an effective treatment nor method of prevention for the deleterious effects caused by Stx intoxication. Antibodies are well recognized as affinity components of therapeutic drugs; thus, a previously obtained recombinant human FabC11:Stx2 fragment was used to neutralize Stx2 in vitro in a Vero cell viability assay. Herein, we demonstrated that this fragment neutralized, in a dose-dependent manner, the cytotoxic effects of Stx2 on human glomerular endothelial cells, on human proximal tubular epithelial cells, and prevented the morphological alterations induced by Stx2. FabC11:Stx2 protected mice from a lethal dose of Stx2 by toxin-antibody pre-incubation. Altogether, our results show the ability of a new encouraging molecule to prevent Stx-intoxication symptoms during STEC infection.